Microwave Assisted Synthesis of Some 3-Benzimidazolyl-5-aryl-cyclohex-3-ene-2-ones - Nyati, M.; Rao, N.S.; Shrivastava, Y.K.; Verma, B.L. (Asian Journal of Chemistry, 2010)
A series of 3-benzimidazolyl-5-aryl-cyclohex-3-ene-2-ones (2a–g) have been synthesized by the reaction of 1-benzimidazolyl-3-(substituted phenyl)-2-propene-1-ones (1a–g) with ethyl acetoacetate in presence of anhydrous K2CO3 and acetone under microwave irradiation.